The color within light is a crucial cue that impacts key metabolites and vitamins in the diatom Odontella aurita - Sansone, Clementina; Russo, Monia Teresa; Paris, Debora; Pistelli, Luigi; Maselli, Maira; Corato, Federico; Tramice, Annabella; Iodice, Annalaura; Margiotta, Francesca; Smerilli, Arianna; Balzano, Sergio; Del Prete, Francesco; et al. (Frontiers in Photobiology, 2025)
The light environment is a key factor regulating the growth and biomass production of microalgae. Photon flux density and spectral composition i.e., the relative contribution of different wavelengths, are among the most important light parameters influencing microalgal efficiency. The red, green and blue bands are used by microalgae as both energy source for photosynthesis and as external cue that triggers biological signaling and physiological adjustments. This study mechanistically explores the effects of light modulation on key metabolites in the emerging model Odontella aurita, the only diatom species currently approved as a food supplement in the EU. Four spectral compositions with red (590–656 nm) ranging from 0% to 60% and blue (422–496 nm) from 60% to 20% were set up under two light conditions: limiting and saturating intensities. Growth and photosynthetic performances were assessed, together with a wide set of metabolites involved in various biochemical pathways including vitamins (A, B1, B2, B6, B8, B9, B12, K1, D2, D3, C and E), auxin, amino acids and other compounds identified by NMR. In addition, the biomass was characterized for its macromolecular composition, carotenoids, phytosterols, total flavonoid and total phenolic content, iron and zinc content, and total antioxidant capacity of the biomass using different assays were evaluated. Results revealed the complementary roles of blue and red lights: blue light enhanced growth and photosynthesis, as well as the use or regulation of photoenergy, whereas red light promoted the regulation of key metabolites e.g., B vitamins or auxin, involved in the modulation of metabolic pathways. These findings provide insight for optimizing diatom cultivation under controlled light environments e.g., with the aim to boost growth and metabolism.